Pengembangan Media Relaksasi Animasi 3D untuk Mengurangi Kecemasan Menghadapi Ujian Siswa SMA - Aprilia, Rosi; Saman, Abdul; Fitriana, Fitriana (Universitas Negeri Makassar, 2025)
This study aims to develop a 3D animation-based relaxation video tutorial to help reduce students’ exam anxiety. The objectives are to (1) identify the need for the media, (2) design its prototype, (3) test its validity, and (4) assess its practicality. The research used a Research and Development (R&D) method with the ADDIE model: analysis, design, development, implementation, and evaluation. Data collection involved interviews, the TAI-G scale, and questionnaires. Ten students from SMAN 2 Luwu Utara joined a small group trial. The results showed that the media was highly needed, with landscape orientation, animated characters, a counseling room background, formal dress, cartoon animation style, balanced colors, and warm lighting. The prototype lasts about 15 minutes with five segments: introduction, breathing relaxation, muscle relaxation, Guided Imagery, and closing. Validation by two material experts scored 93% and 88% (very valid); two media experts gave 98% (very valid). The practicality test by a Guidance and Counseling teacher scored 89% (very practical) and students’ responses reached 92% (very practical). These results indicate that the relaxation video is valid, practical, and feasible for use in Guidance and Counseling services to help students manage exam-related anxiety.